1999
DOI: 10.1080/135468099395954
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis and Conversion Hysteria: A Unifying Model

Abstract: There are many similarities between the symptoms of conversion hysteria and phenomena produced in hypnotic contexts. This paper reviews some of those similarities and considers more general features associated with both hypnotic phenomena and conversion hysteria symptoms such as lack of concern, perceived involuntariness, the display of ''implicit knowledge'' and their apparently compliant nature. Neurophysiological and brain-imaging studies of hypnotically produced effects and conversion symptoms are describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 35 publications
3
79
0
4
Order By: Relevance
“…Similar increases in right IFG activity were found during left hypnotic paralysis using EEG recording [16] in another group of volunteers performing the same Go/NoGo paradigm in normal and hypnotic states. These findings accord with the view that hypnotic suggestions act through modulation of attentional systems that may allow selective filtering of sensory, motor, or even conceptual representations from conscious awareness [18,38,64,73].…”
Section: Dissociation and Hypnosissupporting
confidence: 79%
See 2 more Smart Citations
“…Similar increases in right IFG activity were found during left hypnotic paralysis using EEG recording [16] in another group of volunteers performing the same Go/NoGo paradigm in normal and hypnotic states. These findings accord with the view that hypnotic suggestions act through modulation of attentional systems that may allow selective filtering of sensory, motor, or even conceptual representations from conscious awareness [18,38,64,73].…”
Section: Dissociation and Hypnosissupporting
confidence: 79%
“…In further support of a functional link between deficits produced by conversion and those induced by hypnosis, a few neuroimaging studies have reported that motor paralysis under hypnosis is associated with modulation of brain activity in ACC and ventral prefrontal regions [37,108]. Thus, some recent accounts have proposed that conversion symptoms might be produced by similar cognitive mechanisms as hypnotic suggestion, implicating an active inhibition of the access of sensory or motor representation to conscious awareness [10,64]. To clarify the putative links between these conditions, we also investigated the effect of a hypnotically suggested paralysis on brain activity during the same Go/NoGo motor task as described above (Fig.…”
Section: Dissociation and Hypnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Later study on a larger cohort of subjects confirmed the involvement of orbitofrontal cortex [67], as well as of ACC [11] in hypnotically suggested motor paralysis. Both of these brain areas were proposed to be involved in active inhibition of movement by disconnecting premotor/prefrontal areas from primary motor cortex [45]. A recent EEG study in healthy volunteers reported a distinctive EEG topographic activity pattern during hypnotic paralysis with a specific source in right inferior frontal cortex, as compared to the control condition, indicating the key role of this brain region in executive control mechanisms [8].…”
Section: Hypnosis As a Substitute For Hysteria?mentioning
confidence: 99%
“…Similar behavior has been reported in recent studies of hypnotic blindness and visual conversion disorder (a.k.a. hysterical blindness), in which subjects seem to be influenced by objects or information of which they are apparently unaware (Bryant & McConkey, 1989a-c;Oakley, 1999).…”
Section: Creativity and Hypnosismentioning
confidence: 99%